Кавказ в последний год жизни и творчества Михаила Лермонтова - Jatczak, Grażyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The theme of Caucasia is present in all of Lermontov’s works. In the last year of his life the poet altered the way Caucasia and its inhabitants were perceived. He changed this from a romantic to a realistic description and began the process of deglorifying his characters, as he was interested in the Eastern mentality and philosophy.
Caucasia in the last year of Mikhail Lermontov's life and literary output
Kaukaz w ostatnim roku życia i twórczości Michaiła Lermontowa